2021
DOI: 10.1186/s43094-021-00362-9
|View full text |Cite
|
Sign up to set email alerts
|

Impurity profiling method development and validation of metformin hydrochloride and teneligliptin hydrobromide hydrate in their combination tablet dosage form by using RP-HPLC with UV/PDA detector

Abstract: Background An accurate, precise and robust analytical method was developed for the impurity profiling in the metformin hydrochloride and teneligliptin hydrobromide hydrate tablet. The gradient was optimized for better separation of impurities by using BDS Hypersil C18 250 × 4.6 mm, 5µ column operated at 35 °C. The octane sulfonic acid and phosphate buffer with triethylamine at pH 3.0 were used as mobile phase A, and acetonitrile was used as mobile phase B. The mobile phase was pumped at 1.0 mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…As per pharmacopeia only potentiometry and UV methods are mentioned for Metformin, as per European pharmacopeia and Indian pharmacopeia and as per literature HPTLC [5], HPLC [6,8], UV [6, 9, 10], LC-MS/MS [11] were reported. Even in the mentioned HPLC method, there was a need for an improved and stable method.…”
Section: Metformin Hclmentioning
confidence: 99%
“…As per pharmacopeia only potentiometry and UV methods are mentioned for Metformin, as per European pharmacopeia and Indian pharmacopeia and as per literature HPTLC [5], HPLC [6,8], UV [6, 9, 10], LC-MS/MS [11] were reported. Even in the mentioned HPLC method, there was a need for an improved and stable method.…”
Section: Metformin Hclmentioning
confidence: 99%
“…Bichala et al developed estimation of metformin and teneligliptin in its bulk and tablet dosage form by using the RP-HPLC method . Musmade et al developed the impurity profiling method and validation of metformin hydrochloride and teneligliptin hydrobromide hydrate in their combination tablet dosage form by using the RP-HPLC method . Shah et al developed estimation of antidiabetic drug teneligliptin by the HPTLC method .…”
Section: Introductionmentioning
confidence: 99%
“… 15 Musmade et al developed the impurity profiling method and validation of metformin hydrochloride and teneligliptin hydrobromide hydrate in their combination tablet dosage form by using the RP-HPLC method. 16 Shah et al developed estimation of antidiabetic drug teneligliptin by the HPTLC method. 17 Kumar et al developed teneligliptin by the RP-HPLC method.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the existing literature focusing on the quantitative analysis of TGT and PGZ indicated that efforts have been directed toward devising analytical methods for these individual drugs, as well as in combination with other medications. These efforts have resulted in developing various methods including UV spectroscopy [3,[12][13][14][15], HPLC [2,3,7,[16][17][18][19][20][21][22][23], high-performance thin-layer chromatography (HPTLC) [15,[24][25][26][27][28][29], and LC-MS [23,[30][31][32][33][34][35][36]. Among the various methods that have been reported, the work by Gheewala et al in 2017 provided a comprehensive account of simultaneously determining TGT and PGZ within a synthetic mixture using both UV spectroscopy and HPLC.…”
Section: Introductionmentioning
confidence: 99%